Staging choreographies for team training in multiple virtual worlds based on ontologies and alignments - Silva, Emanuel (2014)
In this paper we present an approach that makes possible the staging of choreographies for education and training purposes in potentially any virtual world platform. A choreography is seen here as the description of a set of actions that must or may be executed by a group of participants, including the goals to be achieved and any restrictions that may exist. We present a system architecture and the formalization of a set of processes that are able to transform a choreography from a platform-independent representation into a specific virtual world platform’s representation. We adopt an ontology-based approach with distinct levels of abstraction for capturing and representing multi-actors and multi-domain choreographies to be staged in virtual world platforms with distinct characteristics. Ontologies are characterized according to two complementary dimensions – choreography’s domain (independent and dependent) and virtual world platform (independent and dependent) – giving rise to four ontologies. Ontology mappings between these ontologies enable the automatic generation of a choreography for virtually any target virtual world platform, thus reducing the time and effort of the choreography development.